Post Partum Uterine Prolapse in a Goat : A Case Report - P.Krishnaveni; Surjith.J.Kumar (The Indian Veterinary Journal, 2025)
This study reports a case of uterine prolapse in a goat. The animal was brought to veterinary dispensary, Mangathotty, Idukki, Kerala with the complaint of prolapse of the uterus after kidding. The animal was recumbent. The everted uterus was cleaned by washing with potassium permanganate solution to remove the gross debris and placenta also removed. Sugar was applied to reduce the edema. Prolapsed uterus was then replaced back in to the pelvic cavity and retention suture was placed to prevent the recurrence. Antibiotics, anti-inflammatory and antihistamine were given.